Professional competences: Strategy for curriculum transformation in Industrial Enginering - Luis Javier Tirado; Jairo Estrada; Raúl Ortiz; Hernando Solano; Diego Alfonso; Guillermo Restrepo; Juan Felipe Delgado; Delfín Ortiz (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
This study presents the concept of competences as successful performance of a job or occupation by effectively combining knowledge, skills, values and attitudes in a defined context. Then the pedagogical and didactical importance of designing a curriculum based on competences is presented, following general procedures that begin with an evaluation of the current training plan, followed by an evaluation of the industrial, professional and social environment. Finally, a competence map, problematical nodes and learning projects are designed.